Analysis of Environmental Impact Aspects of the PT Shipyard. Adiluhung Bangkalan in the Perspective of a Sharia Business Feasibility Study - Veni Vebriyanti; Abdur Rohman (Penerbit Hellow Pustaka, 2024)
Modern activities have become important for human life, where the production process has become more efficient and effective through modern machinery and organized work systems. PT. Adiluhung Saranasegara Indonesia, located in Ujungpiring Village, Bangkalan, East Java, in Indonesia. However, shipyard activities have environmental impacts that need to be addressed. Factors such as pollution, waste management, and environmental degradation can affect the environment. Strategic management at PT. Adiluhung involves environmental education, strategy development, implementation, and evaluation to manage resources and external resources. A comprehensive environmental study, HAZOP, identified potential greenhouse gas emissions and environmental impacts in shipyard operations. Collaboration between government, industry and local communities is essential to reduce environmental degradation and encourage sustainable practices.